Antioxidant activity, total phenolic and flavonoid content of water and ethanol extracts from Achillea millefolium l - Keser, Serhat; Celik, Sait; Turkoglu, Semra; Yilmaz, Ökkes; Turkoglu, Ismail (My University, 2013)
Achillea millefolium (Asteraceae, yarrow) has been used in folk medicine against several disturbances including skin inflammations, spasmodic and gastrointestinal disorders. In this study, ethanol and water extracts were prepared from A. millefolium flowers, leaves and seeds. Antioxidant activities were measured by ferric thiocyanate method, and H2O2 radical scavenging activity assays and phenolic compounds and flavonoid contents of A. millefolium extracts were also determined. In conclusion, extracts of A. millefolium flowers, leaves and seeds had effective H2O2 radical scavenging activity, total antioxidant activity, and these antioxidant activities were compared with BHA and ?-tocopherol as reference antioxidants.
Achillea millefolium L. Su ve Etanol Ekstrelerinin Antioksidan Aktivitesi, Total Fenolik ve Flavonoit İçeri?i
Keywords: Achillea millefolium; Antioxidant; Flavonoid; Total phenolic; Yarrow